(3QMdI GHf GdQTjOs - (3eMeO Hf YeQ Hf eMeO, CHh YHO Gddg, eMH GdOjf GHf QTjO GdagQj GdSHJj,J (B721 (3g` s
(3ChdgG (B:s
(3PcQ JhLgfG ef OeTb MeGgG Gddg JYGdi Edi eOjfI GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3GdCOjH Gdjefi CHj MjGf eMeO Hf MjGf GdMjGfi s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B93s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B836s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdLZQGajG h GdHdOGfs